EKSISTENSI PASAR RAKYAT PASCA ADANYA PASAR MODERN DI KOTA TANGERANG - Agus Iwan Mulyanto (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2019)
The research is based on the idea that the growth of modern markets that is growing rapidly will have an impact on the gap of public market participants where it is necessary to implement government policies to regulate this gap, therefore this study wants to know the existence of people's markets after the existence of a modern market in Tangerang City. The research was a descriptive analytic study using a quantitative approach with a regression method and hypothesis testing with a population of people market participants, each type amounting to 20 people then a sample was taken. Data collection and processing is done by using questionnaires, observations, and interviews, which are analyzed using multiple linear regression techniques with the help of SPSS 20. The results obtained from this study are that the modern market in the form of Modern Market Mall A and Modern Market B has no significant effect (P > 0.05) on the existence of public markets. This is because the visitors to the people's market have their own perceptions so they continue to shop and visit the people's market. Modern markets have a very close relationship with traditional markets. Relationships can be social relations or economic relations